Ecological fragmentation effects in mouse lemurs and small mammals in northwestern Madagascar. Issue 4 (13th October 2019) - Andriatsitohaina, Bertrand; Ramsay, Malcolm S.; Kiene, Frederik; Lehman, Shawn M.; Rasoloharijaona, Solofonirina; Rakotondravony, Romule; Radespiel, Ute
Abstract: Habitat loss and fragmentation are major ecological forces threatening animal communities across the globe. These issues are especially true in Madagascar, where forest loss is ongoing. We examined the effects of forest fragmentation on the distribution and abundance of sympatric, endemic gray, and golden‐brown mouse lemurs ( Microcebus murinus and Microcebus ravelobensis ), the endemic western tuft‐tailed rat ( Eliurus myoxinus ), and the invasive black rat ( Rattus rattus ) in two regions in northwestern Madagascar. We used systematic capture procedures in 40 forest fragments and four continuous forest sites which differed in size, shape, and degree of isolation. With a trapping effort of 11, 567 trap nights during two dry seasons (2017–2018), we captured 929 individuals (432 M. ravelobensis, 196 M. murinus, 116 E. myoxinus, and 185 R. rattus ). We examined the influence of study region, forest type (fragment vs. continuous), forest size, forest shape, the proportion of 50‐m forest edge and distance to continuous forest on the abundance and interaction of the four species. Responses to fragmentation differed strongly between species, but no interaction could be detected between the abundance of the different species. Thus competition within and between native and invasive species may not be regulating abundances in these regions. On the contrary, the abundance of M. ravelobensis and E. myoxinus differed significantly between study regions and was negatively affected by fragmentation. In contrast, there was no evidence of an impact of fragmentation on the abundance of M. murinus . Finally, the invasive R. rattus responded positively to the increasing distance to the continuous forest. In conclusion, the response of small Malagasy mammals to forest fragmentation varies largely between species, and fragmentation effects need to be examined at a species‐specific level to fully understand their ecological dynamics and complexity. Abstract : Small nocturnal lemurs and rats are distributed differently in dry forest landscapes in northwestern Madagascar. Endangered Microcebus ravelobensis and endemic Eliurus myoxinus are more sensitive to fragmentation than the widespread M. murinus and the invasive Rattus rattus. There was no evidence for competition between species Research Highlights: Habitat fragmentation affects the abundance of mouse lemurs and rodents differently. Endangered Microcebus ravelobensis and Eliurus myoxinus are more sensitive to fragmentation than Microcebus murinus and Rattus rattus . There was no evidence for interspecific competition.